Silica Support‐Enhanced Pd‐Catalyzed Allylation Using Allylic Alcohols. Issue 20 (24th October 2018) - Motokura, Ken; Ikeda, Marika; Kim, Minjune; Nakajima, Kiyotaka; Kawashima, Sae; Nambo, Masayuki; Chun, Wang‐Jae; Tanaka, Shinji
Abstract: The front cover artwork for issue 20/2018 is provided by Dr. Ken Motokura at Tokyo Institute of Technology (Japan) and collaborators. The image illustrates the concerted catalysis of a Pd complex and silanol on a mesoporous silica surface for the efficient activation of allylic alcohol in the allylation of nucleophiles. See the Full Paper itself athttps://doi.org/10.1002/cctc.201801097 . Abstract : "The allylic alcohol is activated by a silanol group on the surface of the mesoporous silica support, and then it easily undergoes a π‐allylpalladium intermediate formation. " This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201801097 .